2017
DOI: 10.1039/c7ra09170b
|View full text |Cite
|
Sign up to set email alerts
|

Structured growth from sheaf-like nuclei to highly asymmetric morphology in poly(nonamethylene terephthalate)

Abstract: Thorough microscopy analyses are done on dissecting 3D interiors of poly(nonamethylene terephthalate) (PNT) banded spherulites. Growth of a specific type (Type-I) of banded spherulites is initiated from highly elongated sheaf-like nuclei, with asymmetrically grown lamellae packed as a multi-shell structure, leading to resemblance of a dual-face spheroid. Top-surface bands are characterized with discrete/ unconnected dots of crystals aligned as zig-zag circles, which correspond to interior layered lamellae ends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…An even more advanced study has revealed the shell-like structure in Type-1 ringed PNT spherulites. [35] Figure 12 shows This result is a sufficient and novel evidence to prove that the corrugate-board (flute-liner) structure of the interior ringed PNT spherulites is responsible for the periodic optical banding. Once again, the interior lamellae assembly proves agreement between the crystal periodicity with the optical banding is valid not just for the three types of PTT bands discussed earlier but also for the PNT ringed spherulites (Type-1).…”
Section: Interior Lamellae Assembly In Periodic Bands and Discontinmentioning
confidence: 70%
See 4 more Smart Citations
“…An even more advanced study has revealed the shell-like structure in Type-1 ringed PNT spherulites. [35] Figure 12 shows This result is a sufficient and novel evidence to prove that the corrugate-board (flute-liner) structure of the interior ringed PNT spherulites is responsible for the periodic optical banding. Once again, the interior lamellae assembly proves agreement between the crystal periodicity with the optical banding is valid not just for the three types of PTT bands discussed earlier but also for the PNT ringed spherulites (Type-1).…”
Section: Interior Lamellae Assembly In Periodic Bands and Discontinmentioning
confidence: 70%
“… However, if a fixed T max is used, variation of T c can lead to similar effects of varying the relative fractions of Type‐1 versus Type‐2 ringed PNT spherulites. Figure shows POM micrographs for two ringed types of PNT (Type‐1 vs Type‐2 bands) as function of T c (at 60°C, 65°C, 70°C, or 85°C), respectively, by quenching from T max = 120°C . Very small‐size Type‐1 ringed PNT spherulites are found at lower T c ; on the other hand, larger‐size Type‐1 spherulites are at higher T c 's.…”
Section: Effect Of Chemical Structures Of Aryl Polyesters On Banding mentioning
confidence: 99%
See 3 more Smart Citations